Peningkatan Profitabilitas Melalui Perencanaan Kombinasi Produk Dengan Pendekatan De Novo Programming - Irfan Pratistajati; Miftahol Arifin (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
This study aims to enhance company profitability through product combination planning using the De Novo Programming approach. In a competitive business environment, product combination planning becomes crucial for maximizing profits. By applying De Novo Programming, companies can identify high-profit products based on empirical data. The study evaluates five products produced by the company and highlights the flagship product, X3 (Flange and Spigot Piece), which has proven to yield a significant profit of Rp. 11,062,500,000. Through the allocation of additional budget in the De Novo Programming formulation, the study demonstrates an increase in profit to Rp. 11,858,093,000. This approach aids the company in determining an optimal product combination without the need to produce less popular products, thereby positively impacting overall profitability. By combining empirical analysis and computational approaches, this study provides valuable guidance for companies to make smarter and more profitable planning decisions.